1989
DOI: 10.1139/b89-068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aminocyclopropane carboxylic acid and aminoethoxyvinylglycine on ethylene production by ectomycorrhizal fungi

Abstract: Aminoethoxyvinylglycine, an inhibitor of ethylene production in higher plants, does not inhibit methionine-induced ethylene production by the ectomycorrhizal fungus Laccaria laccata (Scop, ex Fr.) Berk. & Br. Aminocyclopropane carboxylic acid is not a precursor of ethylene formation by L. laccata or Hebeloma crustiliniforme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Indeed, the activation of defense mechanisms in P. deltoides may inhibit L. bicolor colonization, while in P. trichocarpa this inhibition may be repressed by the overexpression of EREBP-4 ethylenesensitive transcription factor. Our results support the conclusions by Felten et al (2010), Rupp et al (1989), and Splivallo et al (2009) that ethylene, released by Laccaria, plays a role in primary response of the host plant. Thus, the initial steps in successful colonization may involve Laccaria manipulating the host's metabolic machinery and subsequently, decreasing their defenses.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the activation of defense mechanisms in P. deltoides may inhibit L. bicolor colonization, while in P. trichocarpa this inhibition may be repressed by the overexpression of EREBP-4 ethylenesensitive transcription factor. Our results support the conclusions by Felten et al (2010), Rupp et al (1989), and Splivallo et al (2009) that ethylene, released by Laccaria, plays a role in primary response of the host plant. Thus, the initial steps in successful colonization may involve Laccaria manipulating the host's metabolic machinery and subsequently, decreasing their defenses.…”
Section: Discussionsupporting
confidence: 91%
“…Impairment of pre-symbiotic lateral root induction in hairy root culture of the auxin-resistant diageotropica tomato mutant suggests that Myc factor-dependent lateral root induction is similarly channeled into the auxin-controlled developmental outcome (Hanlon and Coenen, 2010). Ectomycorrhizal fungi such as Laccaria bicolor and Tuber melanosporum trigger the production of lateral roots prior to colonization through the stimulation of auxin signaling, likely due to their production and release of auxin and ethylene or other volatile compounds (Rupp et al, 1989; Karabaghli-Degron et al, 1998; Ivanchenko et al, 2008; Felten et al, 2009, Felten et al, 2010; Splivallo et al, 2009; Sukumar et al, 2013). Likewise it is possible that also AM fungi produce plant hormones such as auxin and ethylene or other volatile compounds in addition to Myc-LCOs ( Figure 2 ), and this might for example explain SYM pathway-independent lateral root induction in rice, while in nodulating legumes common SYM-mediated lateral root induction might be epistatic to auxin signaling.…”
Section: Lateral Root Induction By Am Fungi Is Regulated At Multiple mentioning
confidence: 99%
“…First, the gas ethylene released by Laccariaand other ECM fungi has already been proposed to play a role in fungal signalling. 2,9 Furthermore, it has been demonstrated that fungi can produce jasmonate derivatives, 10 which may be involved in volatile signalling. Interestingly, exogenously applied ethylene and jasmonates interact with auxin pathways by activating auxin biosynthetic enzymes (Anthranilate Synthase 1-ASA1) and (Tryptophane Amino Transferase-TAA1) in roots and hence stimulate LR formation.…”
Section: Arabidopsis Thaliana and The Ectomycorrhizal Fungus Laccariamentioning
confidence: 99%